EFICACY OF NON-INVASIVE NEUROMODULATION IN REDUCING PAIN INTENSITY AND IMPROVING QUALITY OF LIFE IN PATIENTS WITH DIABETIC NEUROPATHY: A SYSTEMATIC REVIEW AND META ANALYSIS - Dewi, Diana Evita; Febriandha, Alfidha Muntaz Sobrina; Putri, Syarellia Safira; Izzaty, Adzura Qannita Chifka; Kurniawan, Shahdevi Nandar (MNJ (Malang Neurology Journal), 2026)
Background: Diabetic neuropathy (DN) is a common complication of diabetes, resulting in chronic neuropathic pain and impaired quality of life. Pharmacological interventions often demonstrate limited efficacy and some accompanied by adverse effects. Non-invasive neuromodulation (NINM) has emerged as a potential treatment modality. With new RCTs emerging, an review is needed to synthesize the latest evidence. Objective: To evaluate the efficacy of NINM in reducing pain and improving quality of life in DN patients. Method: A systematic search was conducted across PubMed, Cochrane, Sage, Science Direct, Google Scholar, and ProQuest. Only RCTs comparing NINM vs Sham were included. Pain outcomes were measured using NRS and VAS. SF-36 was used to evaluate physical and mental components of quality of life. RevMan 5.4 was used for statistical analysis. Results: Nine studies with 523 participants were analyzed. Significant pain reduction was demonstrated in the NINM group compared to the sham group, as measured by VAS [MD = –1.50, 95% CI –2.40 to –0.60, P = 0.001] and NRS [MD = –0.82, 95% CI –1.40 to –0.60, P < 0.00001]. However, no significant improvement was observed in quality of life, both for the SF-36 physical component [MD = 2.34, 95% CI –0.10 to 4.78, P = 0.06] and the mental component [MD = 6.54, 95% CI -1.55 to 14.64, P = 0.11]. Conclusion: NINM proves effective in pain reduction in DN but shows no improvement in quality of life. Further high-quality trials with longer follow-up are needed to determine its effects on physical and mental components.